1996
DOI: 10.1002/hep.510240609
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized trial comparing lymphoblastoid to recombinant interferon alfa 2a as therapy for chronic hepatitis C

Abstract: the development of IFN-neutralizing antibodies. [12][13][14] TheoretTo compare the long-term effectiveness and tolerabilically, these risks might be enhanced by long-term adminity of lymphoblastoid interferon (IFN-aN1) and recombiistration of a single type of IFN and mitigated by the adminnant interferon alfa 2a (IFN-a2a) in patients with istration of different types of IFN. Lymphoblastoid IFN chronic hepatitis caused by hepatitis C virus (HCV), 234 (IFN-aN1), a mixture of 22 interferons, 15 was shown to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 37 publications
(13 reference statements)
1
12
0
1
Order By: Relevance
“…Genotypes 1a, 3a, and 4 together accounted for less than 20% of patients attending our centre in the 1990s. 19 Patients were also excluded if they had serum hepatitis B surface antigens (HBsAg), daily alcohol intake .60 g for men and .40 g for women, serum antibodies to human immunodeficiency virus, or autoimmune liver disease. Definition of ALT flare An ALT flare was arbitrarily defined as an ALT value >400 IU/l or a maximum/minimum ALT ratio value of >8.…”
Section: Methodsmentioning
confidence: 99%
“…Genotypes 1a, 3a, and 4 together accounted for less than 20% of patients attending our centre in the 1990s. 19 Patients were also excluded if they had serum hepatitis B surface antigens (HBsAg), daily alcohol intake .60 g for men and .40 g for women, serum antibodies to human immunodeficiency virus, or autoimmune liver disease. Definition of ALT flare An ALT flare was arbitrarily defined as an ALT value >400 IU/l or a maximum/minimum ALT ratio value of >8.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of depression has varied substantially across different studies possibly reflecting variation in dosing schedules or in the composition of study cohorts. [27][28][29][30][31][32][33][34][35][36][37] Also, the duration of therapy may play a role. 23,27,32,33,35 Study groups may vary in the proportion of patients with depression.…”
Section: Ifn and Depressionmentioning
confidence: 99%
“…Recent trials have shown convincingly that, similar to other interferons, 21 the optimal duration for treatment with IFNα‐n1 is 12 months rather than 6 months 22 . Although higher doses of some recombinant IFNα have been reported to improve treatment outcomes slightly, 21 –23 this may not be the case for IFNα‐n1 and doses higher than 3 MIU, three times weekly, when administered for 12 months, are associated with an increased rate of adverse effects 24 , 25 …”
Section: Interferon Therapymentioning
confidence: 99%